Hubungan Tingkat Pengetahuan Wanita Usia Subur dengan Perilaku Pencegahan Osteoporosis - Vivin Manora; Jilly Toar; Deviana P. Munthe (Jurnal Ilmiah Kesehatan, 2025)
This study aims to examine the relationship between the level of knowledge about osteoporosis and preventive behavior in suburban women. This study used a quantitative design with an observational analytical approach and a cross-sectional survey. A total of 82 randomly selected respondents were analyzed using the chi-square test. The results showed a significant relationship between knowledge about osteoporosis and preventive behavior. Better knowledge about osteoporosis has been shown to improve preventive behavior carried out by women of childbearing age in the area. With sufficient knowledge, they are more likely to adopt preventive measures to maintain bone health and prevent decreased bone density in the future. This study emphasizes the importance of increasing education about osteoporosis, especially in women of childbearing age, to encourage them to care more about bone health and reduce the risk of osteoporosis in the future. Better education is expected to encourage positive changes in osteoporosis prevention behavior in this age group.